Analisis Komparasi Kelayakan Finansial Usahatani Benih Kentang dengan Sayuran Pakcoy - Putra, Harry Wiyono; Sadeli, Agriani Hermita; Indrawibawa, Diky; Hapsari, Hepi; Djuwendah, Endah (Universitas Galuh, 2024)
Potatoes are one of the alternative carbohydrate sources to replace rice and have a high economic value. According to Badan Pusat Statistik (BPS) in 2023, Indonesia's potato production increased by 4.21 percent from 1.36 million tons to 1.42 million tons. CV. Bumi Agro Technology (CV. BAT) is one of the agribusiness companies which producing potato seeds that affected by the increasing in national potato production. CV. BAT endeavors to extend the cultivation of potato plants land in vegetable fields – in this case, pakcoy plants. The method used in this research employs a qualitative design with a case study approach at CV Bumi Agro Technology. Data were obtained through observation and interviews. This study utilizes Revenue Analysis, Cost Analysis, Income Analysis, Financial Feasibility Analysis RC Ratio, BC Ratio NPV, IRR, Payback of Period, and Profitability Index. The results of this study conclude that potato seed farming and pakcoy cultivation are financially feasible. However, potato seed farming is more financially feasible compared to pakcoy cultivation. CV BAT needs to prioritize potato commodities at the moment, with the note that they should save expenses, especially when purchasing potato seeds and farm consumables.